Dose‐response plasma appearance of green tea catechins in adults. Issue 5 (18th February 2013) - Renouf, Mathieu; Marmet, Cynthia; Guy, Philippe A.; Beaumont, Maurice; Lepage, Mélissa; Williamson, Gary; Dionisi, Fabiola
<x xml:space="preserve">Abstract</x> Scope Tea is an infusion of the Camellia sinensis leaves. The most prevalent bioactive compounds in green tea are catechins (C), which are of great interest for their potential health‐promoting effects. However, metabolism and bioavailability of C are not fully understood. Methods and results This study investigates the human bioavailability (plasma appearance) of C after drinking three doses of infused green tea in a randomized cross‐over design. The sum of area under the curve increased between the small (0.75% w/v, 180 mg total C) and medium (1.25%) dose of ingested green tea but not between the medium and the high (1.75%) dose. The overall pattern for the sum of C did not reflect the fate of individual C. While (–)‐epigallocatechin and 4′‐O‐Me‐epigallocatechin showed saturation in plasma between the medium and high green tea doses, (–)‐epigallocatechin gallate and (–)‐epicatechin did not "saturate" and increased proportionally with the ingested dose. Regardless of the dose, C appeared rapidly in plasma as monophasic curves, suggesting absorption in the small intestine and minimal entero‐hepatic circulation. Conclusion As a conclusion, when studying dose response of polyphenols and metabolites, one must look not only at the overall pattern of plasma appearance, but also at data specific for each metabolite.